Political competition and Mirrleesian income taxation: A first pass - Felix Bierbrauer; Pierre C. Boyer (Max Planck Institute for Research on Collective Goods, 2010)
We study Downsian competition in a Mirrleesian model of income taxation. The competing politicians may differ in competence. If politicians engage in vote-share maximization, the less competent politician's policy proposals are attractive to the minority of rich agents, whereas those of the competent politician are attractive to the majority of poor agents. The less competent politician wins with positive probability, which gives rise to a political failure in the sense of Besley and Coate (1998). Political failures are avoided if politicians maximize winning probabilities. Nevertheless, the two equilibria cannot be Pareto-ranked, the minority may be better off under vote-share maximization.
Keywords: H21; C72; D72; 330; Electoral Competition; Non-linear Income Taxation; Candidate Quality; Wahlkampf; Einkommensteuer; Ökonomischer Anreiz; Optimale Besteuerung; Nichtkooperatives Spiel; Public Choice